FUNCTIONAL ANALYSIS OF CUMULUS CELLS ASSOCIATED GENES RELATED TO THE QUALITY OF IN VITRO FERTILIZED CAPRINE EMBRYOS - M. Elanchezhian; S. Gautham; D. Reena; D. Gopikrishnan; A. Palanisammi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was undertaken to identify the expression of certain genes in cumulus cells as a potential marker for the oocyte quality. Grade A and grade B cumulus oocyte complexes (COCs) were matured and cumulus cells were isolated whereas the oocytes with partial cumulus cells were fertilized. The cleavage rates of grade A oocytes (44.29±1.31) were compared with the cleavage rates of grade B oocytes (34.83±2.72). The developmental rate differences were correlated with the expression of genes (COX2, HAS2, & GREM1) from the cumulus cells of grade A and grade B oocytes. The present result showed that the above said genes express in both grade A and grade B oocytes, irrespective of quality, directing the study towards the quantification of these genes which might bring out a concrete theory behind the mechanism and physiology of the differential expression of these genes in cumulus cells and their feedback on embryo quality.